ACCOUNTING FOR 'INVESTMENT CREDIT' - Woolsey, S. M. (The Accounting Review, 1963)
Abstract The Revenue Act of 1962 provides for an "investment credit" which is generally seven per cent of the qualified investment in depreciable property acquired after December 31, 1961. The "investment credit" may be deducted directly from the amount of federal income tax otherwise payable for the year in which the asset was acquired. For any asset on which the credit is given, the basis of the asset is reduced by the amount of the allowed investment credit for the purpose of determining the amount that may be written off as depreciation over the life of the asset. The investment credit, to the extent that it is fully utilized, should be regarded as a reduction in the tax expenses. This statement is based on the fact that the credit is allowed because of provisions of the revenue act and because it can be of benefit to a company only if there is tax, resulting from taxable revenue, from which the credit can be deducted. The net result of the suggested method and its variations is that a company can take advantage of the income tax law related to the investment credit and still present financial statements which are not unduly affected by the amount or the timing of these tax benefits.